Professional and teaching staff of the Women’s Medical Institute in the fight against epidemics at the beginning of 20th century - A. A. Zhuravlyov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article is devoted to the consideration of the question of how the staff of the St. Petersburg (Petrograd) Women’s Medical Institute participated in the fight against epidemics from the beginning of the century to the 1920s. The use of the Institute’s laboratories and the participation of the staff in the fight against cholera epidemics are considered. The contribution of professors D. K. Zabolotny and S. I. Zlatogorov to the fight against epidemics was noted.